Does cadmium cause cascading effects on the development and reproduction of the striped stem borer, Chilo suppressalis (Walker)? - Hexi Huang; Ning Di; Jie Wang; Yuxing Wang; Zhengyang Zhu; Caige Lu; Su Wang; Liansheng Zang (CABI Agriculture and Bioscience)
Abstract The heavy metal, cadmium (Cd), causing growth retardation and yield reduction on rice and impacting the fitness of organisms inhabiting on rice through bottom-up effects, has become a great challenge to rice production. However, the effect of Cd-exposure on the development of an economically important and destructive rice pest, Chilo suppressalis remains unexplored. By exposing the larvae of C. suppressalis to different Cd-exposed artificial diets (0, 0.2, 1.0, 2.5, 5.0, and 10.0 mg/kg), we found that Cd exposure did not affect the larval duration or pupation rate of C. suppressalis, but caused negative effects on pupal weight at high Cd levels (5.0 and 10.0 mg/kg) and on adult deformity rate from 2.5 and 5.0 mg/kg treatments. Although Cd significantly increased the female pupae ratio, C. suppressalis did not oviposit when Cd treatment was more than 2.5 mg/kg. Meanwhile, Cd transferred to pupae, females, exuviae of pupa and eggs of C. suppressalis from Cd treated larvae, and exhibited a dose-dependent response on Cd accumulation. Our results indicated that Cd had a negative effect on rice stem borer and can be transferred to eggs of C. suppressalis, but more work is needed to further assess the bottom-up effect on third tropic levels in Cd-polluted fields.